Freedom of Speech under Hugo Chávez’ Regime: May, 2007 - Pasquali, Antonio (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2007)
The first part of this text raises the need for an up-to-date and more comprehensive understanding of the concept “freedom of speech”; one that takes into consideration a real praxis and not a mere legal notion; one that takes into account new technological determinants and the contemporary connotations of the term “speech”. The results of the above-mentioned work are then applied in the second part of the text, where the real state of ‘freedom of speech’ in Venezuela, 2007, is described. At the moment, Venezuela is undergoing a rapid political evolution where freedom of expression, even if still respected de jure, is gradually less respected de facto. This section includes a brief empirical description of what could be called the ‘state of the affairs’, an analysis of the new balance between access and participation, plus a final analysis regarding the operative application in Venezuela of Article 19 of the Universal Declaration of Human Rights.